2022
DOI: 10.3390/horticulturae8070618
|View full text |Cite
|
Sign up to set email alerts
|

Crop Diversification Effects on Soil Aggregation and Aggregate-Associated Carbon and Nitrogen in Short-Term Rainfed Olive Groves under Semiarid Mediterranean Conditions

Abstract: Soil particle aggregation and their associated carbon (C) and nitrogen (N) content can provide valuable diagnostic indicators of changes in soil properties in response to the implementation of different agricultural management practices. In this sense, there is limited knowledge regarding the impact of intercropping on soil organic carbon (SOC) and total nitrogen (TN) pools in aggregates. This study aimed to evaluate the short-term effect (4 years) of three crop diversifications in rainfed olive orchards on so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Depending on the site, large (>2000 μm) or small (2000–250 μm) macro‐aggregates were the more prone fractions to changes several years after SLM implementation. In line with these results, González‐Rosado et al (2022) found a higher large macro‐aggregates percentage, but no change in small macro‐aggregates, after 3 years in an olive woody crop diversified with saffron. However, other studies have observed the opposite, or even an increase in both large and small macro‐aggregates (Veloso et al, 2019).…”
Section: Discussionmentioning
confidence: 55%
“…Depending on the site, large (>2000 μm) or small (2000–250 μm) macro‐aggregates were the more prone fractions to changes several years after SLM implementation. In line with these results, González‐Rosado et al (2022) found a higher large macro‐aggregates percentage, but no change in small macro‐aggregates, after 3 years in an olive woody crop diversified with saffron. However, other studies have observed the opposite, or even an increase in both large and small macro‐aggregates (Veloso et al, 2019).…”
Section: Discussionmentioning
confidence: 55%
“…, human activities; Ilay & Kavdir, 2018 ). Agricultural management measures, such as leaving the soil bare or plowing can lead to macro aggregate turnover and soil instability ( González-Rosado et al, 2022 ). The topsoil had the best soil stability in the SL but the deeper soil had the best soil stability in the GL ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The carbon content of a soil is important in Mediterranean systems based on intensive cultivation, which, if not addressed, leads to notable losses of the soil organic matter content, especially in arid and semi-arid areas where soils are often already very poor in organic matter content [72]. Table 2 shows the values of the NECB obtained at the end of the experiment.…”
Section: Net Carbon Balance In Aerobic Environments Of Rice (Necb)mentioning
confidence: 99%